A water-carbon-economic model coupling system dynamics and InVEST for Wuhan’s sustainability assessment - Yixuan Diao; Jun Xia; Qianjin Dong; Qiting Zuo; Mengyun Xie; Xiaofeng Peng; Long Jiang (Ecological Indicators, 2025)
Understanding the interactions between water security, carbon storage, and economic and social development (WCE) is critical for achieving sustainable urbanization. This study establishes a coupled WCE system model for Wuhan, China, by integrating System Dynamics (SD) and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model to quantify dynamic socioeconomic processes and spatial ecological patterns. A mechanical model was further employed to quantify system coordination and assess urban sustainability. Future scenarios were simulated to identify optimal development pathways. The results showed: (1) During the historical period (2000–2020), green economic and social development enhanced resource utilization efficiency (+289%) but reduced ecological security levels (−41%). (2) WCE system coordination improved (0.45 → 0.68), while the primary constraint shifted from water scarcity to carbon storage deficit. (3) Future scenario simulations (2021–2030) indicate declining coordination under baseline scenario, whereas the low-carbon green strategy achieves optimal coordination (>0.8), significantly outperforming ecological protection and high-intensity urbanization strategies. This work provides the first quantitative assessment of WCE interactions and coordination status in megalopolises along the Yangtze River Basin, demonstrating the advantage of SD-InVEST coupling in integrating socioeconomic dynamics with ecosystem spatial processes. The proposed framework offers a scientific tool for comprehensive urban planning incorporating water-carbon-economy nexus, with the low-carbon green pathway identified as essential for enhancing sustainability.